2020
DOI: 10.1016/j.transci.2020.102993
|View full text |Cite
|
Sign up to set email alerts
|

Potential of therapeutic plasmapheresis in treatment of COVID-19 patients: Immunopathogenesis and coagulopathy

Abstract: Therapeutic plasmapheresis (TP) is the process of the separation and removal of plasma from other blood components and is considered as an adjunctive treatment strategy to the discarded abnormal agent in the management of respiratory viral pandemics. This article reviews the mechanisms of immunopathogenesis and coagulopathy induced by SARS-CoV-2 and the potential benefits of TP as adjunctive treatment in critically COVID-19 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 37 publications
0
52
0
1
Order By: Relevance
“…This therapeutic potential can be of use as an adjunctive treatment for the management of cytokine storm and coagulopathy in COVID-19 respiratory viral pandemics. 18 Although the relationship between COVID-19 and HUS has not been fully clarified, preliminary results of a study on the effectiveness of C5 inhibitor eculizumab, an important agent that has been used in the treatment of atypical HUS in recent years, in suppressing inflammation in moderate-severe coronavirus-related cases have also been published. 19 , 20 Eculizumab treatment was among the next-line treatments considered after the initiation of plasmapheresis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This therapeutic potential can be of use as an adjunctive treatment for the management of cytokine storm and coagulopathy in COVID-19 respiratory viral pandemics. 18 Although the relationship between COVID-19 and HUS has not been fully clarified, preliminary results of a study on the effectiveness of C5 inhibitor eculizumab, an important agent that has been used in the treatment of atypical HUS in recent years, in suppressing inflammation in moderate-severe coronavirus-related cases have also been published. 19 , 20 Eculizumab treatment was among the next-line treatments considered after the initiation of plasmapheresis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmapheresis has been reported to have positive outcomes in COVID-19 patients. 24 , 25 The obvious drawback to this would be the lack of resources to undergo plasmapheresis for every hemodynamically unstable COVID-19 patient with signs of coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, timely initiation of plasmapheresis within this period could determine better health outcomes. It is also necessary to administer TP for the correct duration and quantity to monitor the possible drug removal of speci c therapies and to follow the treatment outcome [27]. The effect of plasmapheresis in sepsis has shown that both the timing and disease severity are important for the bene cial effect of the procedure [28].…”
Section: Discussionmentioning
confidence: 99%